Kepadatan CD8 di Lingkungan Mikrotumor pada Subtipe Diffuse Large B Cell Lymphoma - Indah Yunalda; Krisna Murt; Aida Farida; Ika Kartika; Erial Bahar (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2021)
BackgroundDiffuse Large B Cell Lymphomas (DLBCL) is divided into two subtypes, GCB and non-GCB, which are determined based on Hans'salgorithm. The GCB subtype has a better prognosis than non-GCB. Some studies indicate that the tumor progression wasinfluenced by tumor microenvironment, including CD8+ TILs located both surrounding tumor cells and peripheral. This study aims todetermine the density of CD8+ TILs in the tumor microenvironment of DLBCL subtypes.MethodsA Cross sectional study of 40 samples of DLBCL registered to Department of Anatomical Pathology Faculty of Medicine UniversitasSriwijaya/Dr. Mohammad Hoesin Palembang Hospital from 1st October 2017 to 31st December 2018. All samples were stained usinganti-CD8 antibody, afterward, lymphocytes express CD8 were assessed both in surrounding tumor cells and peripheral. The densityof CD8 in each DLBCL subtype was analyzed statistically using Mann Whitney U Test.ResultsIn this study, non-GCB subtype was found higher in comparison to GCB subtype (72.5%) and the samples was dominated by youngages (75%). Significantly, peripheral CD8 density was higher than that of surrounding tumor cells, both in the GCB (p=0.003) andnon-GCB subtypes (p=0.000).ConclusionIn both subtypes, CD8 density is higher in peripheral than surrounding tumor cells and a high density in surrounding tumor cells willbe followed by an increase in peripheral CD8 density.